Hypoxia inducible factors as mediators of reactive oxygen/nitrogen species homeostasis in physiological normoxia. (August 2019) - Stuart, Jeffrey A.; Aibueku, Odosa; Bagshaw, Olivia; Moradi, Fereshteh
Abstract: Although once considered by biologists almost exclusively for their toxicity, reactive oxygen (ROS) and nitrogen (RNS) species produced within normal cells under baseline physiological conditions are now appreciated as redox regulators of a wide range of protein functions. Two families of enzymes, the NADPH oxidases (NOXs) and nitric oxide synthases (NOSs), are major sources of ROS/RNS from molecular oxygen. Aquaporins (AQPs) are membrane channels capable of transporting some ROS/RNS, in particular hydrogen peroxide and perhaps nitric oxide. The activities of all these enzymes and channels are sensitive to variations in oxygen levels within the physiological range experienced by cells in the human body. Since ROS/RNS have important physiological roles and their endogenous production is affected by oxygen levels, we hypothesize that the synthesis of these proteins is increased at lower oxygen levels within the physiological range of most human cells in vivo, i.e. 2–5%, in order to facilitate the maintenance of ROS/RNS production rates. We further postulate that this is achieved, at least in part, by transcriptional stimulation mediated by the activity of hypoxia inducible factors (HIFs), which are strongly regulated by oxygen levels over the same range of oxygen. Here we survey the evidence supporting this hypothesis, including induction of expression of NOXs, NOSs, and AQPs at lower oxygen levels, presence of hypoxia response elements in the corresponding human genes, and evidence from chromatin immunoprecipitation (ChIP) experiments that HIF-1 and/or HIF-2 bind these regions. We find a significant amount of empirical data supporting the hypothesis that HIFs could function as physiological regulators of ROS/RNS homeostasis in the normoxic range in human cells.